CREATING PUBLIC ENVIRONMENTAL AWARENESS THROUGH MUSIC: “PLAY FOR NATURE” PROJECT - Bıcakcı, A.Banu (European Scientific Journal, ESJ, 2013)
This paper examines a voluntary initiative named ‘Play for Nature’ that utilizes music as a mediator to create public environmental awareness. Strengths and weaknesses of the project are scrutinized from a public relations viewpoint. Data is collected via related media coverage followed by an online interview held by the initiator and organizer of the project in Turkey, Fırat Çavaş. It is concluded that the project that is able to reach millions of people, by using the powers of music and social media, should be managed with a strategic communication approach, as to fulfill the main objective. The study offers Play for Nature an applicable communication frame for the future chapter of the project.